Application Assessment Method Using Teacher Rating Scale And Profile Matching: Application Assessment Method Using Teacher Rating Scale And Profile Matching - Ratih Mardianti; Agung Triayudi; Ira Diana Sholihati (Institute of Computer Science (IOCS), 2020)
In education in school, the teacher is an importent figure in determining the hight and low qualityof educatin outcomes, so teacher is required to cotinue to improve the performancein teaching, and ensure teacher performance the need for assessment, at ach school, teacher assesment is still i the form of manual of the principal as the party who assesses teacher performance, while not everytime the principal monitors how the teacher’s performance in teaching, it is necessary to add other more intensive assesors to meet with the teacher, namely students with several conditions that make students eligible to be correspondents, and a teacher assessment application to support students assessing their teacher more easily, making the application using the Rating Scale method for taking initial grade data and Profile Matching for calculating the average final grade. The results of the testing of this program is that 100% accuracy is tested from 6 teachers and 20 students